Diphenylalanine-based degradable piezoelectric nanogenerators enabled by polylactic acid polymer-assisted transfer. (October 2021) - Tao, Zhen; Yuan, Hui; Ding, Su; Wang, Yong; Hu, Wen; Yang, Rusen
Abstract: Biocompatible and biodegradable energy harvesters are of significance for biomedical application as an alternative energy source without causing adverse effects to the human body. Intrinsically biocompatible diphenylalanine peptides with good piezoelectric, dielectric, and mechanical properties are promising materials for energy conversion. Herein, we report a degradable piezoelectric nanogenerator (PENG) based on a free-standing polylactic acid film with embedded diphenylalanine microrods arrays. The stiff polylactic acid polymer can remove stiff microrods from rigid silicon substrate and transfer uniformly external forces to them for energy conversion. The PENG produces a maximal output voltage of 1.78 V and a power density of 1.56 W m −3 . Furthermore, the device exhibits full dissolution in alkaline solution, acidic solution and phosphate-buffered saline solution after 25 days at 60 ℃. The degradable PENG provides a viable solution to power transient electronics and reduce the environmental footprint of devices. Graphical Abstract: A degradable PENG based on biological FF peptides have been developed, which can be entirely dissolved in basic, acidic, and neutral solution. Owing to the rational design that utilizing PLA film to unify the external force, the device has exhibited good output performance. The degradable and biocompatible PENG will provide a viable solution to power transient electronics and wearable technology. ga1 Highlights: A free-standing PLA film with FF microrods embedded was achieved and it enabled the fabrication of a flexible and thin PENG. The good match of the stiffness of the PLA polymer and FF peptides enables a high performance of the PENG. The FF-based PENG can be fully degraded in basic, acidic, and neutral solution.